Автоматична система дозування рідини - Фільчакова, Д. Є. (ХНУРЕ, 2021)
The given work is devoted to modern approaches of fluid dosage in modern automation production for different operations. This system is designed to control the processes of dosing and cost accounting of components. It allows you to dose substances in a given time or logical sequence. The automatic system of liquid dosing for washing of printed circuit boards allows to do process of washing in the automatic mode with the minimum influence of the person and accurate dosing.
Keywords: автоматична система дозування рідини